The role of biology and culture in Veblenian consumption dynamics - Christian Cordes (Max Planck Institute of Economics, 2007)
This paper incorporates aspects of humans' evolved cognition into a formal model of cultural evolution and scrutinizes their interactions with population-level processes. It is shown how the biased transmission of different kinds of behavior via cultural learning processes influences agents' consumption behavior. Thereby, the model's learning dynamics are capable of generating typical Veblenian consumption dynamics. Based on these insights, the paper then scrutinizes on the role of humans' biological heritage and Darwinian concepts in the development of economic theories in general. Moreover, the relation of the ontological basis of biological and cultural evolution is addressed.
Keywords: B41; B52; A12; D11; C60; 330; Conspicuous consumption; Economic theory development; Evolutionary economics; Darwinism; Cultural evolution; Konsuminterdependenz; Evolutionsökonomik; Bioökonomik; Sozialer Wandel; Theorie